Udział Bolesława Kominka w pracach Konferencji Episkopatu Polski i jej komisji specjalistycznych (1956–1974) - Białkowski, Michał (Studia Pastoralne, 2020)
Bolesław Kominek played a considerable role in the work of the Polish Bishops’ Conference (KEP) and its special committees. He had been a formal member of the KEP since 1954, but in practice he had participated in its sessions since 1956. From 1958 he had been a member of the Main Committee of the Polish Episcopate. His activity embraced several areas: preparing pastoral letters, addresses and messages; involvement in establishing relations with the Polish government (under the Communist regime); contributions to regulating the status of the Catholic Church in the western and northern parts of Poland; academic work pertaining to the reorganization of the structures of the Polish church administration; contacts with the Holy See, other bishops’ conferences and Vatican organizations. A major area of his activity on the forum of the Polish Bishops’ Conference was his work in special committees. In the period of twenty years of his service as a bishop, Bolesław Kominek had been a member of the following committees: General Pastoral Committee of the Polish Episcopate – chairman in 1968-1974; Iustitia et Pax Committee of the Polish Episcopate – assistant and chairman in 1968-1974; Committee on the Church in the Western and Northern Parts of Poland of the Polish Episcopate – chairman in 1970-1972; Committee for Pastoral Charity of the Polish Episcopate – member in 1958-1967; Marian Committee of the Polish Episcopate – member in 1958-1974; Council Committee of the Polish Episcopate – member in 1963-1970. This dedicated and creative activity of the Bishop of Wrocław shows not only the scope of his pastoral involvement, but also helps to discover the depth of his original vision of the Church, to better evaluate his impact on the ecclesial reality after the war, and to appreciate his role as a spokesman for the Western and Northern parts of Poland.